Dampak Zikir Khafi terhadap Ketenangan Jiwa pada Pengamal Tarekat Qadiriyah Naqsabandiyah - Rahmadan Arifin; Idrus Alkaf; Heni Indrayani (Jurnal Spiritual Healing, 2022)
Peace of mind is a very universal expression of happiness experienced by people. Peace of mind has a very strong bond with dhikr, which is a verbal and spiritual worship activity that is expressed by saying certain sentences using the heart to mention Allah's name without an outward sound. The purpose of this study is to find out the method of practicing the Qadiriyah Naqsyabandiyahi Order and the impact of remembrance of kahfi on peace of mind for the practitioners of the Qadiriyah Naqsyabandiyah Order in Air Limau Village. This research method uses descriptive qualitative research methods, with data collection techniques, namely by observation, interviews, and documentation. The results of this study indicate that the Qadiriyah Naqsyabandiyah Order is a combination of two orders, namely the Qadiriyah Tarekat and the Naqsyabandiyah Order. The Qadiriyah Naqsyabandiyah Order was founded by Sheikh Ahmad Khotib Syambas Ibn Abd.Ghaffar al-Sambasi al-Jawi (d.1878 AD) in 1857 AD. The procedure for the congregation is by coming to a murshid to take bai'at or making a promise to practice it. the teachings of the Qadiriyah Naqshbandiyah Order. The activities of the Qadiriyah Naqsyabandiyah Order by practicing the remembrance of Jahar, remembrance of khafi, khataman, manaqiban, riyadoh, and pilgrimages to the tomb of Mursyid. The visible impact when finished dhikr khafi is that it can cause a sense of energy in the soul, relieve stress, be solemn in worship, be passionate about worship, and always surrender to Allah for all trials or calamities and tests that come from Allah SWT.